DOMESTICATION, FOREIGNIZATION, AND LEXICAL DENSITY: ENGLISH TRANSLATIONS OF “METAI“ (SEASONS OF THE YEAR) BY KRISTIJONAS DONELAITIS - KALĖDAITĖ, VIOLETA (Knygotyra, 2015)
The rural epic “Metai” (Seasons of the Year) by Kristijonas Donelaitis, a milestone of Lithuanian literature, has enjoyed the status of similar literary writings viewed as a ‘must’ for being translated into different languages. Up to now, translations of “Metai” have appeared in 13 different languages (Armenian, Byelorussian, Czech, English, Georgian, German, Hungarian, Latvian, Polish, Russian, Spanish, Swedish, and Ukrainian). As regards translations into English, the poem was not translated in full until 1967; the translation was carried out by Nadas Rastenis and published in Los Angeles. The other complete translation of “Metai” is almost 20 years apart, performed by Peter Tempest and published in 1985. The present analysis aims to find out which of the opposing strategies – foreignization or domestication – is more consistently employed in the two English translations (on the macrolevel). The specific research questions on the micro-level concern two text properties, lexical density and lexical diversity, in the source-text and the two translations. These parameters were evaluated using corpus linguistics methodology and tools. The overall evaluation of the domesticating and foreignizing strategies employed in the two translations demonstrates that each of them is applied to a certain degree. The domestication is fair, revealing respect for the original, the author and the reader, whereas foreignizing strategies are mainly seen on the discoursal, generic level. The translators tried to balance the two approaches for the target reader to be able to appreciate both, the specificity of the cultural content and the fluent domesticated narrative. As for the lexico-semantic level, the highest lexical density was found in the analyzed Lithuanian data (excerpts from the poem), reaching over 62%, while the two translations show statistically important lower density, roughly about 54% each. This means that about 8% of content words were lost in the translations. With respect to lexical diversity, N. Rastenis with a 789-word text seems to be more loquacious than P. Tempest (the total number of words – 654).
Keywords: domestication; foreignization; culture-specific items; lexical density; lexical diversity (richness)